Single Photon Manipulation - Xia, Keyu (IntechOpen, 2020)
This short book aims to present basic information about single photons in a quick read but with not many details. For this purpose, it only introduces the basic concept of single photons, the most important method of generating single photons in experiments, and a specific emerging field.